Sustainable Development Goal indicator for measuring availability and affordability of medicines for children: a proof-of-concept study - Fatima Suleman; Aukje K Mantel-Teeuwisse; Hendrika A van den Ham; Iris R Joosse (BMJ Open, 2023)
Objectives To complement Sustainable Development Goal (SDG) indicator 3.b.3 that monitors access to medicines for all, a corresponding child-specific methodology was developed tailored to the health needs of children. This methodology could aid countries in monitoring accessibility to paediatric medicines in a validated manner and on a longitudinal basis. We aimed to provide proof of concept of this adapted methodology by applying the method to historical datasets.Method A core set of child-appropriate medicines was selected for two groups of children: children aged 1–59 months and children aged 5–12 years. To enable calculation of affordability of medicines for children, the number of units needed for treatment was created, incorporating the recommended dosage and duration of treatment for the specific age group. The adapted methodology was applied to health facility survey data from Burundi (2013), China (2012) and Haiti (2011) for one age group. SDG indicator 3.b.3 scores and (mean) individual facility scores were calculated per country and sector.Results We were able to calculate SDG indicator 3.b.3 based on historical data from Burundi, China and Haiti with the adapted methodology. In this case study, all individual facilities failed to reach the 80% benchmark of accessible medicines, resulting in SDG indicator 3.b.3 scores of 0% for all 3 countries. Mean facility scores ranged from 22.2% in Haiti to 40.3% in Burundi for lowest-price generic medicines. Mean facility scores for originator brands were 0%, 16.5% and 9.9% for Burundi, China and Haiti, respectively. The low scores seemed to stem from the low availability of medicines.Conclusion The child-specific methodology was successfully applied to historical data from Burundi, China and Haiti, providing proof of concept of this methodology. The proposed validation steps and sensitivity analyses will help determine its robustness and could lead to further improvements.